Effect of physiotherapeutic procedures on the bioelectric activity of the masseter muscle and the range of motion of the temporomandibular joints in the female population with chronic pain: a randomized controlled trial - Magdalena Gębska; Bartosz Dalewski; Łukasz Pałka; Paweł Kiczmer; Łukasz Kołodziej (BMC, 2023)
Summary Introduction Physical therapy (PT) methods applied in dentistry are increasingly discussed nowadays. Taking into account a rapidly growing number of temporomandibular disorders (TMDs) and orofacial pain patients, it is reasonable to determine which of the available physiotherapeutic (PT) methods are more effective than others, especially in terms of their possible analgesic and myorelaxant effects. Objective To assess manual and physical factors influencing pain reduction or elimination and increased muscle tension in patients with TMD; yet the influence of the applied forms of PT on the range of motion (ROM) of temporomandibular joints (TMJ). Material and methods A randomized, parallel-group, RCT, single-blind, equi-randomized (1:1) study was conducted in DC/TMD Group Ib patients (20-45 years of age). An experimental group (G1, n = 104) and a control group without TMD (G2, n = 104) were created according to CONSORT guidelines. Diagnostic measurements were performed in both groups (mass sEMG, temporomandibular joint range of motion-ROM, pain intensity - NRS). Group G1 was randomly divided (envelope method) into 4 therapeutic groups, in which therapy was carried out for 10 days: magnetostimulation (MS), magnetoledotherapy (MLE), magnetolaserotherapy (MLA), manual therapy (MT). Each time after the therapy, ROM and NRS measurements were performed, and after the 5th and 10th day sEMG. Results Statistically significant differences were found in the sEMG values of the masseter muscles, TMJ ROM and the pain intensity in G1 and G2 (p < 0.00). The largest decrease in sEMG (% MVC) of the masseter muscle occurred in the subgroup in which the manual therapy (MT) procedures were applied, p < 0.000. There was no clinically significant difference in and between other subgroups. There was a distinct mandible ROM increase noted in the MT group, with minimal changes in the MLA and MLE groups and no changes in the MS group. There was a clear increase in the lateral mobility of both right and left TMJ in the MT group. There were no differences in the course of the study in the MS group, and slight increases in the MLA and MLE groups. In the case of pain measurements, the greatest decrease in pain intensity was observed in the MT subgroup. Conclusions According to our results manual therapy is an effective form of treatment in patients with pain, increased masticatory muscle tension and limitation in mandible ROM. Dental physiotherapy should become an integral part of multimodal TMD patients' treatment.